PENGATURAN MENU MAKAN DAN PEMBERIAN TABLET TAMBAH DARAH PADA IBU NIFAS DI PMB KABUPATEN SIMALUNGUN TAHUN 2019 - Sukaisi Sukaisi; Zuraidah Zuraidah; Lenny Nainggolan (Jurnal Salam Sehat Masyarakat (JSSM), 2020)
Anemia in the postpartum period may be associated with an increased prevalence of shortness of breath, fatigue, palpitations and maternal infections, especially of the urinary tract. The effect of anemia during the puerperium is the occurrence of uterine subvolution which can cause post-partum hemorrhage, eases puerperal infection, decreases breastfeeding and it is easy to develop maternal infection. Measurement of hemoglobin levels, knowledge, provision of materials, training in eating menu settings, monitoring and evaluation. The audience in this devotion are postpartum mothers with postpartum >1 week from PMB R. Harianja, T. Hutapea, Hendrayatni, and Ika Juliana in the Simalungun Regency and surrounding areas, who are anemic and willing to be trained on food menu management totaling around 40 people. Out of 52 postpartum mothers whose hemoglobin levels were measured, 40 experienced anemia and attended training activities on dietary management and blood supplementation. Postpartum mothers who participated in the service activities consisted of 14 primiparous people, and 26 multiparous people. Measurement of Hb levels obtained initial measurement results of 9.2 gr% - 10.8 g%, with the category of mild anemia. Interviews with several postpartum mothers, some routinely drank tea 1-2 / day. The information is needed about how to consume ferrum, related to the culture of drinking tea and it is hoped that postpartum mothers who have attended training become agents for other postpartum mothers.